A beginner's guide to bioinformatics. (28th April 2023) - Patel, Krutik
Abstract : Bioinformatics has revolutionized the modern life sciences and has become a component of many undergraduate training courses and post-graduate research projects. As such, we are seeing more bioinformatics and programming aspects within undergraduate training and so it is important to understand what bioinformatics is, why it is a necessity in modern research and how young academics can begin their journey as bioinformaticians. This article outlines the broad spectrum of what bioinformatics is used for within research labs and provides several resources for beginners to learn how to code and perform bioinformatic tasks.